Techniques and Outcomes in Microsurgical Treatment of Posttraumatic Lymphedema: A Systematic Review - Dahl, Victoria A.; Tadisina, Kashyap K.; Hale, Eva; Fullerton, Natalia; Mella-Catinchi, Juan; Xu, Kyle Y. (Journal of Reconstructive Microsurgery, 2024)
Background The microsurgical treatment of lymphedema has been well-studied and has been shown to be effective, especially in cancer-related lymphedema. Posttraumatic lymphedema (PTL) is a debilitating condition that remains understudied and underreported, and surgical techniques for PTL treatment are not well-represented in the literature. The purpose of this study was to systematically review all published reports of physiologic surgical interventions for PTL.Methods A search was conducted on PubMed, MEDLINE, Embase, and Web of Science, from January 1, 2000 to December 6, 2022, using keywords “PTL,” “lymphedema,” and “surgery” to identify reports of PTL treated with microsurgical lymphatic reconstruction techniques. PTL cases treated with ablation, debulking, or decongestive therapy were excluded.Results A total of 18 records that met the inclusion criteria were identified, representing 112 patients who underwent microsurgical operations for PTL. This included 60 cases of lymph flow restoration (LFR) via lymph axiality and interpositional flap transfer, 29 vascularized lymph node transfers, 11 lymphatic vessel free flaps, 10 lymphovenous anastomoses (LVAs), and 2 autologous lymphovenous transfers. Outcomes were primarily reported as clinical improvement or LFR by lymphatic imaging. All studies showed qualitative improvement of symptoms and reports with quantitative data showed statistically significant improvements.Conclusion PTL is currently underrepresented in lymphedema treatment literature, however, our results show that microsurgical techniques are successful in treating lymphedema in PTL patients. Increasing awareness of PTL and establishing standardized diagnostic criteria and treatment options will help clinicians better understand how to diagnose and treat this condition. Prospective and comparative studies are needed to determine true prevalence of PTL and optimal treatment strategies.
Keywords: posttraumatic lymphedema; trauma lymphedema; lymphovenous bypass; lymphovenous anastomosis; vascularized lymph node transfer